On the design of integrated modular avionics assisted by formal modeling. - Fabiano Costa Carvalho (2009)
Avionics system manufacturers are currently facing the problem of developing highly-integrated systems under economic pressures. In this scenario, the empirical approach, characterized by trial and error techniques, is not adequate since the correction of design flaws is often related to expensive re-work and schedule overruns. The evolution of airborne systems toward Integrated Modular Avionics (IMA) pushes the need for advanced methods that could enforce correctness of complex designs while minimizing the chances of introducing errors. Considering this problem, this work proposes a systematic conceptual design strategy based on formal methods, aiming at improving the development processes for IMA systems. The basic idea is to concentrate efforts on the construction, simulation, and formal analysis of a mathematical model for the new system at early development lifecycle phases. The proposed approach was exercised on a case study of practical avionics project in order to evaluate the drawbacks and advantages. Results suggest that this work could contribute to the aeronautics industry by offering alternative means to cope with complexity in modern avionics projects.